Kepastian Hukum Terkait Pengambilalihan (Akuisisi) Saham Dalam Suatu Perseroan Terbatas Tertutup Dengan Akta Jual Beli Saham - Mujaddady Mujaddady; Ilham Ilham (Universitas Sains dan Teknologi Komputer, 2024)
The use of a Share Sale and Purchase Deed in the context of taking over shares in a Closed Limited Company is a legal issue which is the basis of this research. Buying and selling shares and acquiring shares is often considered a problem in notarial practice, and differences in interpretation regarding ratification of notarial deeds arise depending on the notary's obligation to ratify notarial deeds. Because there are no regulations that specifically support this, it is necessary to discuss the status of this legal issue. The research method uses a normative juridical research type, with a statutory-regulatory approach, case approach, historical approach, and context approach. The results of this research: that the use of a Share Sale and Purchase Deed can be carried out as long as there is no change in control, however if the implementation of the share sale and purchase results in a change in control, then it is best to do so. carried out through procedures, conditions and procedures for taking over shares (acquisition). This legal position is closely related to the role of the Notary in making deeds, which must always minimize the existence of deeds from the environment in the future. Legal certainty regarding the takeover of shares (acquisition) of a Closed Limited Company with a Share Sale and Purchase Deed, where if the sale and purchase of shares does not result in a change in share ownership, then the use of the sale and purchase deed provides certainty for the parties, however if the sale and purchase of shares results in a change control of shares, then the sale and purchase deed does not provide legal certainty for the parties, so it must be carried out in accordance with procedures and mechanisms. arrange share acquisition.